The Pancreatitis Activity Scoring System Predicts Clinical Outcomes in Patients With Infected Pancreatic Necrosis. Issue 6 (July 2021) - Thiruvengadam, Nikhil R.; Miranda, Janille; Kim, Christopher; Behr, Spencer; Arain, Mustafa A.
Abstract : Objectives: The Pancreatitis Activity Scoring System (PASS) is an objective tool validated in acute pancreatitis but not in infected pancreatic necrosis (IPN). Our aim was to evaluate the role of PASS in IPN. Methods: We performed a retrospective cohort study of IPN patients admitted to the University of California, San Francisco from January 2011 to March 2019. Daily PASS scores were calculated for each patient. Receiver operator characteristic analysis was used to define the optimal cutoff PASS score to predict outcomes. The primary and secondary outcomes were 72 hours postintervention multiorgan failure (MOF) and early readmission (within 30 days), respectively. Results: One hundred and four patients underwent intervention (median age, 55 years). Thirty-five patients (33.6%) developed MOF postintervention. A 72-hour postintervention PASS greater than 250 was strongly associated with postintervention MOF (area under curve, 0.87; adjusted odds ratio, 26.83; 95% confidence interval, 6.37–112.86; P < 0.001). Discharge PASS greater than 150 was associated with 30-day readmission (area under curve, 0.82; adjusted odds ratio, 26.44; 95% confidence interval, 8.48–82.43; P < 0.001). Conclusions: The PASS score was associated with postintervention clinical outcomes and early readmission, suggesting it is a valid measure of disease activity in patients with IPN. Further prospective validation of PASS in IPN is needed. Abstract : Supplemental digital content is available in the text.